Using OECD Patient Reported Indicators Study (PaRIS) to generate the Population Health Survey - Puntoni, Sarah; Cox, Sally (International Journal of Population Data Science, 2025)
Objectives Wales participation to OECD PaRIS offered a unique opportunity to gather over 25,000 health outcomes and experiences of adults over 45 living in Wales. These structured questionnaires are now being linked to other nationally held datasets to understand the impact on daily lives and activities for those with chronic conditions. Methods In 2023, Wales PaRIS data collection saw 75 GP practices completing the Provider Survey and over 25,000 adults over 45 complete the Patient Survey. These questionnaires were developed by a scientific committee on behalf of OECD Member States to undertake the first outcome based international benchmarking study of adults managed in primary care (PaRIS). Wales implementation allowed for patient identifiable data to be collected that could be linked to nationally held data sets (hospital activity data, mortality, emergency care etc.), providing a unique opportunity to understand outcomes and experiences of the Welsh adult population through a Value Based Healthcare lens. Results The large data set is generating valuable insights into variation of outcomes between regions (rural vs city), people’s characteristics (sex, age, income etc) and diseases. Initial analysis shows that patients with multi morbidity have lower PROMIS scores across four domains – physical health, mental health, general health, and social functioning. The Population Health Survey data alongside activity and testing data is revealing new understanding into the communication and self-management needs of individuals with various risk factors and clinical outcomes. This will guide us in supporting people with different needs to better manage their care. Additionally, we are using this information to understand the impact of pain on people’s daily activities and outcomes, to drive improvement in the way we coordinate and manage people’s pain and conditions. Conclusion Wales participation in PaRIS has provided the perfect opportunity to undertake an adult population needs assessment for Wales. The data insights being generated are of an unprecedented scale and quality, thanks to its implementation model, that allows its wider use within our NHS Wales data ecosystem.